2001
DOI: 10.1097/00002030-200108004-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of key parameters of sexual behaviour in four African urban populations with different levels of HIV infection

Abstract: In these four African populations, differences in reported sexual behaviour could not explain the differences in rate of spread of HIV. In all four cities, high-risk sexual behaviour patterns were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 13 publications
5
70
1
Order By: Relevance
“…Two articles reported on the same data, and their information was therefore combined in the analysis, and they were treated as one study. 12,13 Information about sample characteristics, setting, study design, variables adjusted for and statistical results were extracted from the study by one reviewer (NK), and a confirmatory data extraction and quality appraisal were carried out by a second reviewer (HS). The quality appraisal was conducted using seven appraisal questions adapted from the graphical appraisal tool for epidemiological studies (GATE).…”
Section: Methodsmentioning
confidence: 99%
“…Two articles reported on the same data, and their information was therefore combined in the analysis, and they were treated as one study. 12,13 Information about sample characteristics, setting, study design, variables adjusted for and statistical results were extracted from the study by one reviewer (NK), and a confirmatory data extraction and quality appraisal were carried out by a second reviewer (HS). The quality appraisal was conducted using seven appraisal questions adapted from the graphical appraisal tool for epidemiological studies (GATE).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, we find that men in Kisumu maintain ongoing relationships with nonmarital sexual partners. In fact, men's nonmarital relationships in Kisumu were the longest recorded in a comparative study across four African cities (Ferry et al 2001). Relationship duration also varies significantly by male economic status: Wealthier men's relationships are approximately 14 months in duration on average compared to approximately 12 months on average for poorer men.…”
Section: Female Partner Characteristicsmentioning
confidence: 98%
“…Research in rural Malawi has shown that the husbands of HIV-positive women are more likely to be HIV positive and, in rural Uganda, especially if they are ten or more years older (Bracher et al, 2003;Kelly et al, 2003). Analysis revealing a negative correlation between median age at first marriage and HIV prevalence in four sub-Saharan African cities also supports the argument of the risks of early marriage (Ferry et al, 2001).…”
Section: Introductionmentioning
confidence: 84%